The Content of Educational Values in the Wuku Galungan Tradition in Wonomulyo, Magetan, East Java - Wibowo, Anjar Mukti; Hartono, Yudi; Hermansyah, Luluk (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Wonomulyo is known as a tourist village of the land above the clouds. The people of Wonomulyo manage their lives based on ancestral heritage values, with the concept of harmony based on the local wisdom of the Wuku Galungan tradition, a tradition to commemorate the death of Ki Hajar Wonokoso. This research reveals the historical background, procession, and content of educational values of the Wuku Galungan tradition in facing various challenges. The data were obtained through observation, in-depth interviews, and document analysis using ethnography. The data were then analyzed through the interactive analysis model to interpret the phenomenon. The results show that 1) the historical background of the Wuku Galungan tradition came from the legend of Ki Hajar Wonokoso, who died on the Tuesday Wage Wuku Galungan; 2) the Wuku Galungan tradition was executed in the area of Ki Hajar's tomb on the Tuesday Wage with a kind of thanksgiving and visiting processions; 3) the Wuku Galungan tradition had religious values which is reflected in the belief that there is a great power outside humans in obtaining blessings from God, tolerance, love for the environment and other living creatures; mutual cooperation reflected in the sambatan (splice) tradition; as well as nature and cultural conservation reflected in the harmony concept of the people of Wonomulyo in facing various challenges.